Cost-effectiveness of exercise referral schemes: a systematic review of health economic studies. (4th December 2021) - Werbrouck, Amber; Schmidt, Masja; Putman, Koen; Seghers, Jan; Simoens, Steven; Verhaeghe, Nick; Annemans, Lieven
Abstract: Background: This systematic review aimed to provide an overview of the existing literature on cost-effectiveness of exercise referral schemes (ERSs). Methods: A systematic search was performed in MEDLINE, EMBASE, EconLit, Web of Science and PsycINFO. Main inclusion criteria were: (1) insufficiently active people; (2) ERSs and (3) full health economic evaluations. No publication year limits were applied. The methodological quality was assessed independently by two reviewers using the Consensus Health Economic Criteria (CHEC) checklist. Results: Fifteen eligible publications were retrieved, presenting results of 12 different studies. Compared with usual care, ERSs were found to be cost-effective in a majority of the analyses, but with modest health gains and costs per individual. These cost-effectiveness results were also sensitive to small changes in input parameters. Two studies found that ERSs combined with a pedometer/accelerometer are cost-effective, compared with usual ERS practice. Two other studies found that an ERS with phone support and an ERS with face-to-face support might be equally effective, with similar costs. Conclusion: Although the literature demonstrated that ERSs could be cost-effective compared with usual care, these results were not robust. Based on a small number of studies, ERSs could be optimized by using tracking devices, or by providing a choice to the participants about the delivery mode. There is need for clarity on the effectiveness of and attendance to ERS, as more certainty about these key input parameters will strengthen health-economic evidence, and thus will allow to provide a clearer message to health policy-makers.